Aplikasi Network Inventory Collection System Untuk Medukung Perencanaan Investasi Teknologi Informasi - Sukmaaji, Anjik; Jusak, Jusak (Journal JCONES, 2012)
The growth of Information Technology (IT) investment is predicted to develop rapidly in the next few years. This will urge the need of a tool to help IT managers to manage and monitor their asset frequently. In this paper, we identify components that will contribute significantly to the planning of IT investment. The results were derived from a survey that was done in three big cities that might be considered as a representative of IT development in Indonesia, i.e. Jakarta, Surabaya and Denpasar (Bali). Based on the results of the survey, we have built a tool for managing and monitoring the IT assets, including configuration system, devices, storage media, interfaces and installed applications. The tool is utilizing the simple network management protocol (SNMP) for querying all IT assets information from each client/agent in a network.